2009
DOI: 10.1063/1.3077305
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of plasma ablation using inverse wire array Z pinches

Abstract: An inverse (exploding) wire array configuration, in which the wires form a cylinder around a current carrying electrode on axis, was used to study the ablation phase of the wires. This configuration allows the parameters of the plasma from individual wires of the array to be measured as the ablated plasma streams propagate in the outward radial direction. The density distribution and the evolution of the natural mode of modulation of the ablation flow was measured with interferometry and soft x-ray imaging. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…From the end of the current pre-pulse and until ∼140-160 ns (depending on wire diameter used) the generator current remains in the inverse wire array. During this time the wires of the inverse array behave in the same way as wires in standard, imploding wire arrays [9]. The wires remain stationary at their initial positions and ablate plasma which flows radially outwards.…”
mentioning
confidence: 81%
“…From the end of the current pre-pulse and until ∼140-160 ns (depending on wire diameter used) the generator current remains in the inverse wire array. During this time the wires of the inverse array behave in the same way as wires in standard, imploding wire arrays [9]. The wires remain stationary at their initial positions and ablate plasma which flows radially outwards.…”
mentioning
confidence: 81%
“…Previous work has shown that the ablation rate along the length of each wire core is modulated at a well-defined wavelength (k $ 0.25 mm for W), 21 and that this leads to a modulation of the ablation stream density (typical amplitude $50%). 22 Apart from these regular modulations in density, the overall dynamics along the array length are uniform, and thus, our axial average should give a good handle on the overall array dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from the short resistive phase, the voltage across the inverse array wires (measured at the top of the central cathode rod) remains very low until the explosion of the array. 25 When the explosion begins, the impedance (resistance and inductance) of the wires, and therefore the voltage across them, rapidly increases. This characteristic voltage history makes the inverse array a promising, compact tool for rapidly switching current into a load.…”
Section: Experimental Setup and Overview Of Two-stage Wire Array mentioning
confidence: 99%
“…B. Overview of the operation of a two-stage wire array z-pinch Inverse arrays have been shown to exhibit the same ablation dynamics as standard wire array z-pinches, with the exception that the ablation flow is directed radially outwards. 25,26 At the beginning of the generator current pulse, energy is deposited into the array wires via resistive heating. This "resistive phase" lasts for $20 ns and ends when plasma forms on the surface of the wires.…”
Section: Experimental Setup and Overview Of Two-stage Wire Array mentioning
confidence: 99%
See 1 more Smart Citation